2016
DOI: 10.9781/ijimai.2016.3713
|View full text |Cite
|
Sign up to set email alerts
|

Chinese-chi and Kundalini yoga Meditations Effects on the Autonomic Nervous System: Comparative Study

Abstract: -Cardiac disease is one of the major causes for death all over the world. Heart rate variability (HRV) is a significant parameter that used in assessing Autonomous Nervous System (ANS) activity. Generally, the 2D Poincare′ plot and 3D Poincaré plot of the HRV signals reflect the effect of different external stimuli on the ANS. Meditation is one of such external stimulus, which has different techniques with different types of effects on the ANS. Chinese Chi-meditation and Kundalini yoga are two different effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…4, N is the number of RR intervals, D + i is the distance of ith point above the LOI, and D i is the distance of ith point from the LOI given by: It is reported that HRA index of meditators (Chi and KYM) are significantly different from non-meditators especially at higher delays [42,43]. Similarly, Rohila and Sharma [43] observe that there occurs a significant increase in GI index too during meditation, (2) while Goshvarpour et al [27,35] have observed that SD1/SD2 ratio also increases during meditation, which connotes the dominant parasympathetic activity, while Dey et al [49] have presented a 3D frequency delay plot, which shows that the effect of Chi and KYM on the ANS are not alike, rather their impacts are completely opposite. Goswami et al [33] use a modified version of Poincaré plot, termed as the second-order difference plot and observe that during meditation (Chi and KYM), the axis of the cluster rotates anticlockwise.…”
Section: Application Of Poincaré Plotsmentioning
confidence: 98%
“…4, N is the number of RR intervals, D + i is the distance of ith point above the LOI, and D i is the distance of ith point from the LOI given by: It is reported that HRA index of meditators (Chi and KYM) are significantly different from non-meditators especially at higher delays [42,43]. Similarly, Rohila and Sharma [43] observe that there occurs a significant increase in GI index too during meditation, (2) while Goshvarpour et al [27,35] have observed that SD1/SD2 ratio also increases during meditation, which connotes the dominant parasympathetic activity, while Dey et al [49] have presented a 3D frequency delay plot, which shows that the effect of Chi and KYM on the ANS are not alike, rather their impacts are completely opposite. Goswami et al [33] use a modified version of Poincaré plot, termed as the second-order difference plot and observe that during meditation (Chi and KYM), the axis of the cluster rotates anticlockwise.…”
Section: Application Of Poincaré Plotsmentioning
confidence: 98%
“…The growth of fully automated face-based affect detection. Peter Robinson and his team have worked on the use of facial expressions for affect detection (Dey et al, 2016;Robinson, 2004). Other projects aim to use facial expression recognition techniques to improve the interaction between students and learning systems (Arroyo, 2009;McDaniel, 2007).…”
Section: Detection Of Affective Computingmentioning
confidence: 99%
“…Meditation has a profound effect on HRV. Several studies have investigated the effect of breathing on HRV [2]. Along with linear measures of HRV, studies have shown that nonlinear measures of HRV are sensitive to changes in breathing pattern but not light exercise [3].…”
Section: Introductionmentioning
confidence: 99%